2009
DOI: 10.1186/1748-717x-4-22
|View full text |Cite
|
Sign up to set email alerts
|

Implications of a high-definition multileaf collimator (HD-MLC) on treatment planning techniques for stereotactic body radiation therapy (SBRT): a planning study

Abstract: Purpose: To assess the impact of two multileaf collimator (MLC) systems (2.5 and 5 mm leaf widths) on three-dimensional conformal radiotherapy, intensity-modulated radiotherapy, and dynamic conformal arc techniques for stereotactic body radiation therapy (SBRT) of liver and lung lesions.Methods: Twenty-nine SBRT plans of primary liver (n = 11) and lung (n = 18) tumors were the basis of this study. Five-millimeter leaf width 120-leaf Varian Millennium (M120) MLC-based plans served as reference, and were designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…The biggest gains were seen for complex target shapes 7. Tanyi et al performed a planning study comparing the M120 to HD‐MLC for liver and lung with 3D, IMRT, and VMAT treatment plans and found small differences between the MLC types with the biggest difference being the faster dose falloff with the HD‐MLC 8. Dhabaan et al examined the benefit of the HD‐MLC for intracranial radiosurgery planning with dynamic conformal arcs and found that conformity and dose gradients were both improved with the HD‐MLC 9…”
Section: Discussionmentioning
confidence: 99%
“…The biggest gains were seen for complex target shapes 7. Tanyi et al performed a planning study comparing the M120 to HD‐MLC for liver and lung with 3D, IMRT, and VMAT treatment plans and found small differences between the MLC types with the biggest difference being the faster dose falloff with the HD‐MLC 8. Dhabaan et al examined the benefit of the HD‐MLC for intracranial radiosurgery planning with dynamic conformal arcs and found that conformity and dose gradients were both improved with the HD‐MLC 9…”
Section: Discussionmentioning
confidence: 99%
“…One of the important studies to assess the impact of MLC on dose distribution was performed by Bortfeld et al (4) They showed that theoretically calculated optimum leaf width for 6 MV photon beam was in the range of 1.52.0 mm. The dosimetric benefit of thin leaf MLCs has been investigated for small target using IMRT technique 5 , 6 , 7 , 8 , 9 , 10 . Tanyi et al (10) analyzed the impact of two MLC systems for linear accelerator‐based intracranial SRS using three‐dimensional conformal radiotherapy (3D CRT), IMRT, and DCRT.…”
Section: Discussionmentioning
confidence: 99%
“…The dosimetric benefit of thin leaf MLCs has been investigated for small target using IMRT technique 5 , 6 , 7 , 8 , 9 , 10 . Tanyi et al (10) analyzed the impact of two MLC systems for linear accelerator‐based intracranial SRS using three‐dimensional conformal radiotherapy (3D CRT), IMRT, and DCRT. They found a small dosimetric advantage of 2.5 mm leaf width MLC system over 5 mm MLC system in terms of dose conformation, normal tissue exposure, and a rapid dose falloff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These advancements can include flattening filter‐free (FFF) technology 1 , 2 to achieve high dose rates, image‐guidance capabilities (including MV, 3 , 4 kV, (5) and CBCT (6) imaging), high‐definition MLC widths for enhanced beam shaping, 7 , 8 abilities for real‐time tumor tracking, (9) motion management, 10 , 11 and a patient positioning system 12 , 13 to enable submillimeter precision in target localization.…”
Section: Introductionmentioning
confidence: 99%